Effect of decaffeinated green tea and green coffee combination on improving blood glucose levels in metabolic syndrome patients - Nugroho, Ira Vori; Rohman, Mohammad Saifur; Karolina, Wella; Tjahjono, Cholid Tri; Kurnianingsih, Novi (Universitas Brawijaya, 2026)
Background: Metabolic syndrome (MS) contributes to high mortality and morbidity not only in developing countries but also in developed countries, with central obesity and insulin resistance as primary risk factors. Our previous study demonstrated that combined decaffeinated green tea and green coffee extracts more effectively improved lipid and glucose profiles in an MS rat model. Objective: This study evaluates the efficacy of the extracts on top guideline-directed medical treatment optimal therapy in metabolic syndrome patients. Methods: The study was a randomized controlled trial (RCT) involving 90 patients diagnosed with metabolic syndrome, ages 45-70. Participants were randomly sorted into three groups: the first group received 2x2.5 g, the second group received 1x5 g, and the third one received a placebo. Researchers measured baseline and final values for fasting blood glucose (FBG), post-meal glucose levels (PPBG), and glycated hemoglobin (HbA1C) to evaluate treatment effects. Result: After 90 days of treatment with decaffeinated green tea and green coffee combination, both experimental groups (Groups 1 and 2) revealed significant decreases in PPBG and HbA1c compared to the control group. (-14.10 ± 2.00 vs. -28.63 ± 4.61 vs. -5.03 ± 0.74 mg/dL and -0.23 ± 0.01 vs. -0.22 ± 0.03 vs. -0.13 ± 0.01; p = < 0.05). FBG decreased across all groups but was not statistically significant. Conclusion: After 90 days, the combination of decaffeinated green tea and green coffee significantly reduced PPBG and HbA1C levels in patients with metabolic syndrome compared to the placebo. These findings suggest that this combination may serve as an effective adjunctive therapy for glucose management in metabolic syndrome, translating efficacious preclinical dosages to clinical application.